Kannimar Shrines and Iconography: A Set of Tamil Folk Goddesses Interpreted in a Pan-Indian Context - Beck, Brenda E. F. (Religions of South Asia, 2021)
The Kannimar are seven look-alike goddesses affiliated with the Pleiades. In local Tamil folk temples of Tamilnadu’s Kongu area they are worshipped in one cluster, as sisters. They are mediators who occupy a middle ground, both spatially and ritually. The seven are served together, soon after the most prominent gods and goddesses, but ahead of other deities, mainly devotees and service-providers whose shrines are found in the same broad compound. The seven Kannimar provide a key bridge linking local to pan-Indian belief traditions. Their role resembles that of certain women in the human sphere, where it is common for a mother to mediate between father and son, or for a sister to bridge the awkward gap between her family of birth and that of her in-laws. The Kannimar also operate as handmaidens dedicated to the service of the great goddess Kali. They are her loyal communicators and errand runners. These seven females are youthful charmers, but they are also fierce womb-guardians who have nurturing powers and awesome resurrection abilities. The relative placement of the Kannimar within the local folk universe, can offer us multiple insights into a wide range of human and divine relationships expressed through the Hindu pantheon.